2020
DOI: 10.1016/j.amsu.2020.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Stroke care and outcomes in the Department of Neurology in Parakou, Benin: Retrospective cohort study

Abstract: Introduction Stroke is one of the most common causes of high mortality rates in Africa with many unknown aspects around its prognosis. In this study we aim to describe stroke characteristics and in-hospital mortality of stroke in Parakou. Methods This is a retrospective cohort study including all stroke patients admitted to the Department of Neurology at Parakou Teaching Hospital from January 1, 2013 through to December 31, 2019. Clinical data, vascular risk factors, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…However, despite the high stroke mortality rates in Africa, little is known about stroke subtypes and prognosis, 11 stroke awareness among health professionals is lacking, 12,13 and there is a scarcity of stroke units and health services. 14,15…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the high stroke mortality rates in Africa, little is known about stroke subtypes and prognosis, 11 stroke awareness among health professionals is lacking, 12,13 and there is a scarcity of stroke units and health services. 14,15…”
Section: Introductionmentioning
confidence: 99%
“…In summary, our study in a large cohort of stroke patients from the Conakry stroke registry identified a predictive model for favorable stroke outcomes with an AUC similar to predictive models in HIC 12 , 15 , 33 . There were four modifiable variables: early brain CT imaging, fever, sores and mean blood pressure increased the proportion of stroke favorable outcome variability explained by the model beyond admission NIHSS.…”
Section: Discussionmentioning
confidence: 56%
“…Indeed, the combination of admission NIHSS and age was found to be highly predictive of favorable stroke outcome in several studies, outperforming other clinical or imaging-based scores in HIC 12 , 14 . In our population, we found that age failed to predict better outcomes than HIC-based models, where age is consistently associated with outcome prediction 33 35 . This specificity in our population is likely because our population is almost fifteen years younger than in the HIC stroke studied populations 28 , 29 , 33 35 , with over a quarter of the patients who experience stroke before fifty years old in Guinea 21 .…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations